A Very Rare Cause of Pleuritic Chest Pain: Bilateral Pleuritis as a First Sign of Familial Mediterranean Fever. (17th January 2013) - Ozkaya, Sevket; Butun, Saliha E.; Findik, Serhat; Atici, Atilla; Dirican, Adem
Abstract : The familial Mediterranean fever (FMF), also called recurrent polyserositis, is characterized by reccurrent episodes of serositis at pleura, peritoneum, and synovial membrane and fever. We present a patient with recurrent bilateral pleural effusion due to serositis attacks as a first sign of FMF. A 59-year-old Turkish man suffered from recurrent pleuritic chest pain due to pleural effusion and atelectasis. The etiology was not found, and his symptoms were spontaneously recovered during several weeks. The pleuritic chest pain was associated with abdominal pain in the last attack. The gene mutation analysis revealed the homozygosity of FMF (F479L) gene mutation in both our patient and his grandchild. After the colchicine treatment, the attack has not developed. In conclusion, recurrent pleural effusion and pleuritic chest pain may be the first signs of the FMF.